Collecting and evaluating convalescent plasma for COVID‐19 treatment: why and how?. Issue 6 (3rd May 2020) - Tiberghien, Pierre; de Lamballerie, Xavier; Morel, Pascal; Gallian, Pierre; Lacombe, Karine; Yazdanpanah, Yazdan
Abstract : Plasma provided by COVID‐19 convalescent patients may provide therapeutic relief as the number of COVID‐19 cases escalates steeply worldwide. Prior findings in various viral respiratory diseases including SARS‐CoV‐related pneumonia suggest that convalescent plasma can reduce mortality, although formal proof of efficacy is still lacking. By reducing viral spread early on, such an approach may possibly downplay subsequent immunopathology. Identifying, collecting, qualifying and preparing plasma from convalescent patients with adequate SARS‐CoV‐2‐neutralizing Ab titres in an acute crisis setting may be challenging, although well within the remit of most blood establishments. Careful clinical evaluation should allow to quickly establish whether such passive immunotherapy, administered at early phases of the disease in patients at high risk of deleterious evolution, may reduce the frequency of patient deterioration, and thereby COVID‐19 mortality.